Vol.2 - O'Connor, David E. (New Delhi, 2006)
There is no doubt that we live in a truly global economy - Japanese automobiles are manufactured in American plants and exported to Europe; McDonald's Golden Arches beckon to customers in over 100 countries; skyrocketing oil prices have a ripple effect on the cost of thousands of goods worldwide. "Encyclopedia of the Global Economy" illuminates these issues and many more, covering a wide spectrum of concepts, people, and organizations related to economic globalization from its origins in the quest for exotic spices in the 16th century to the debates and controversies that reflect it today. Volume 1 features over 150 entries, organized alphabetically, with definitions and descriptions, examples, photographic illustrations, references, and exhibits featuring the most current data. The topics include: international trade; corporate social responsibility; foreign investment; child labor; transnational corporations; sustainable consumption; economic and human development and the digital divide; and, offshore outsourcing. This volume also includes profiles of prominent economists, business leaders, and policymakers as well as a timeline of major events and a glossary of key concepts and institutions. Volume 2 includes a wide array of primary documents, a "data bank" of world statistics on demographic and economic trends, and print and Internet resources for further research. Each document is introduced with an explanation of its context and linked to related articles in Volume 1. Examples include the text of the North American Free Trade Agreement (NAFTA), reports on environmental degradation and poverty reduction from the United Nations, and dozens of tables and graphs reflecting international investment, business activity, productivity, labor, and socioeconomic conditions around the world. Cross-referenced throughout, featuring a comprehensive index, and cutting across such disciplines as politics, sociology, and business, this unique reference will be an indispensable resource for students, teachers, businesspeople, and general readers interested in the dynamics of the global economy and its profound impact on nations, businesses, communities, and individuals.
Keywords: Economic development